The Usborne book of discovery. (London : Usborne Pub, 1994)
Contents.--Inventors / Struan Reid and Patricia Fara.--Scientists / Struan Reid and Patricia Fara.--Explorers / Felicity Everett and Struan Reid.
Keywords: Inventors -- Juvenile literature; Scientists -- Juvenile literature; Explorers -- Juvenile literature